A COMPARISON OF MALE AND FEMALE GESTATIONAL AGE CHILDREN’S VOCABULARY MASTERY OF BUGIS LANGUANGE IN BUCINRI VILLAGE - Fajeri, Ince Nurul; Amir, Johar; Aj, Andi Agussalim (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This study aims to describe the Bugis vocabulary mastery of preschool-age children in Bucinri village, Pangkep Regency. This research is qualitative in nature using observation, interviews and documentation, with data analysis through collection, reduction, presentation and drawing conclusions. The results show that children's vocabulary mastery is quite good, with the majority of respondents recognizing and using 155 vocabulary words. Similarities in vocabulary mastery between boys and girls in 6 word classes with a total of 52 vocabularies. Girls excel at nouns, numeralia and adverbs, while boys excel at verbs, adjectives and pronouns. This research suggests attention to the area of language acquisition to support children's development according to the needs of each group.